(untitled) (CIENCIA Y TECNOLOGÍA AGROPECUARIA, 2023)
This study investigated the symbiotic relationship between microbiota and cocoa agroforestry plantations, focusing on how this interaction enhances abiotic stress tolerance under adverse conditions such as droughts, salinity, and climate changes. A systematic literature review methodology was employed, wherein articles were selected from academic databases using specific inclusion criteria to ensure the relevance and quality of the analyzed information. The research highlighted how the diversity and presence of soil microorganisms significantly contribute to the resilience of cocoa through improved nutrient uptake, root system strengthening, and the activation of physiological responses. These mechanisms underscore the ability of cocoa plantations to cope with abiotic stress and emphasize the importance of promoting such interactions for the sustainable development of the crop under varying environmental conditions. Furthermore, practical implications for agricultural management were discussed, focusing on enhancing soil microbiota health and diversity through sustainable agronomic practices and the use of beneficial microorganisms. These strategies are vital not only for cocoa production but also for global food security. In conclusion, the study provides evidence supporting the implementation of more effective and sustainable management strategies that enhance the productivity and resilience of agroforestry systems in response to climate change and other environmental pressures, thereby contributing to the maintenance of agricultural and ecological sustainability.